A novel heat sink for cooling concentrator photovoltaic system using PCM-porous system. (5th March 2021) - Duan, Juan
Graphical abstract: Highlights: Novel heat sink consisted of PCM and metal foam is used to cool CPV. The cooling effect of PCM-porous is much better than pure PCM. Small porosity or larger height could improve electric efficiency. An optimized range of porosity and height is shown. Abstract: A novel heat sink composed of phase change material (PCM) and metal foam (porous) is investigated in this study, which is used to cool the concentrator photovoltaic (CPV) at a solar concentration ratio (CR) of 20. The effects of the PCM-porous systems with different porosities ( ε = 80%, 90%, 100%) and heights ( H = 0.5x, 1.0x, 2.0x, 3.0x) on improving the electric efficiency of CPV modules are numerically studied. The results show that the metal foam with high thermal conductivity embedded in PCM with high latent heat can significantly enhance the cooling effect of CPV compared to the pure PCM as the heat sink. When the CPV is cooled by the PCM-porous, the electric efficiency of the solar cell increases with the decrease of the porosity. However, the duration time which could maintain the CPV in a constant temperature decreases with the decrease of the porosity. The height of PCM-porous is another factor to influence the cooling effect and electric efficiency of the solar cell. When the porosity is the same, increasing the height ( H ) of the cavity of PCM-porous from 0.5x to 1.0x could increase the electric efficiency and power productivity around to 50%. But increasing the height from 1.0x to 2.0x has little effect on improving the electric efficiency. When the porosity is less than 100%, increasing the height from 2.0x to 3.0x would slightly decrease the electric efficiency.